SOCIAL MEDIA AS A PROMOTION MEDIA FOR SIJANGKU PINEAPPLE DODOL BUSINESS IN SAMBAS DISTRICT: Case Study in UMKM Mawar Merah - Agustia, Dini; Kurniati*, Dewi; Fitrianti, Wanti (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2022)
During the Covid-19 pandemic, which began to occur in 2020, resulted in a decline in sales of various MSMEs, one of which was the Mawar Merah UMKM, which produced processed pineapple lunkhead products. The reason is the limited meeting of MSME owners during the pandemic and the lack of promotion on social media. Therefore, this study aims to determine priorities and alternative methods of promotion through social media, as well as develop appropriate promotional strategies to increase sales. This study used a descriptive quantitative survey method with the help of the Analytic Hierarchy Process (AHP) software from Expert Choice 11 software. A total of 21 research respondents conducted purposive sampling by deliberately distributing the electronic questionnaire link via Google Forms. The results of this study indicate that the priority criteria for promotion of dodol pineapple sijangku is context criteria, the main priority in the sub-criteria is providing informative information accompanied by pictures, while the main priority for alternative promotion is context strategy. Keywords : AHP, Sijangku Pineapple Dodol, Promotion, Social Media, MSMEs